High-Affinity Zinc Inhibition of NMDA NR1–NR2A Receptors - Paoletti, Pierre (J Neurosci, 1997)
Micromolar concentrations of extracellular Zn(2+)are known to antagonize native NMDA receptors via a dual mechanism involving both a voltage-independent and a voltage-dependent inhibition. We have tried to evaluate the relative importance of these two effects and their subunit specificity on recombinant NMDA receptors expressed in HEK 293 cells and Xenopus oocytes. The comparison of NR1a–NR2A and NR1a–NR2B receptors shows that the voltage-dependent inhibition is similar in both types of receptors but that the voltage-independent inhibition occurs at much lower Zn(2+) concentrations in NR1a–NR2A receptors (IC(50) in the nanomolar range) than in NR1a–NR2B receptors (IC(50) in the micromolar range). The high affinity of the effect observed with NR1a–NR2A receptors was found to be attributable mostly to the slow dissociation of Zn(2+) from its binding site. By analyzing the effects of Zn(2+) on varied combinations of NR1 (NR1a or NR1b) and NR2 (NR2A, NR2B, NR2C), we show that both the NR1 and the NR2 subunits contribute to the voltage-independent Zn(2+) inhibition. We have observed further that under control conditions, i.e., in zero nominal Zn(2+) solutions, the addition of low concentrations of heavy metal chelators markedly potentiates the responses of NR1a–NR2A receptors, but not of NR1a–NR2B receptors. This result suggests that traces of a heavy metal (probably Zn(2+)) contaminate standard solutions and tonically inhibit NR1a–NR2A receptors. Chelation of a contaminant metal also could account for the rapid NR2A subunit-specific potentiations produced by reducing compounds like DTT or glutathione.